Double Crosslinked Polymer Electrolyte by C–S–C Group and Metal–Organic Framework for Solid‐State Lithium Batteries. Issue 3 (8th December 2022) - Xu, Ruogu; Xu, Shengjun; Wang, Fei; Xiao, Ru; Tang, Pei; Zhang, Xiaoyin; Bai, Shuo; Sun, Zhenhua; Li, Feng
Abstract : Poly(ethylene oxide) (PEO) is among the most promising candidates for solid‐state electrolytes in lithium metal batteries. However, the low ionic conductivity caused by strong coordination between Li ions and the EO chains limits the practical application of PEO‐based electrolytes. Herein, a double crosslinked PEO‐based electrolyte with alternate C–S–C groups and functionalized metal–organic frameworks (MOFs) is proposed. The incorporation of C–S–C groups not only accelerates Li ions transport by weakening the coordination between Li ions and polymer backbone, but also facilitates segmental relaxation of the polymer backbone. The PEO‐based electrolyte with C–S–C groups shows a remarkable 13‐fold increase in ionic conductivity. Furthermore, when functionalized MOFs are used as crosslinked centers, the double‐crosslinked PEO‐based electrolyte with a robust network structure possesses enhanced mechanical/electrochemical/thermal stability and limited anion transmission. As a result, the symmetrical Li||Li cell enables over 2400 h cycling at room temperature. The LiFePO4 ||Li cells show long cycle life over a wide temperature range from 25 to 100 °C, and a high areal capacity of 1.43 mAh cm −2 is achieved with a cathode loading of 10.0 mg cm −2 . This study demonstrates a promising strategy to develop advanced electrolytes for potential solid‐state lithium‐metal batteries. Abstract : The double crosslinked poly(ethylene oxide) (PEO)‐based electrolyte with C–S–C group and metal–organic framework is prepared for solid‐state lithium batteries. The double crosslinked electrolyte structure demonstrates improved mechanical/electrochemical/thermal stability and limited anion transmission. Moreover, the incorporation of C–S–C groups in the PEO backbones can create a weakly coordinating environment and fast chain motion in the PEO‐based electrolyte.